Efektivitas kombinasi buerger allen and resistance exercise terhadap gula darah puasa dan adekuasi hemodialisis pasien diabetic kidney disease - Afriza, Wicke; Astika, Tria; Rayasari, Fitrian; Natashia, Dea (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Diabetic nephropathy is another term for diabetic kidney disease. patients with diabetes and diabetic kidney disease constitute a distinct population group diagnosed with increased urinary albumin excretion or decreased glomerular filtration rate (GFR). This impacts kidney function and alters the way waste and excess fluid are removed from the body. Purpose: To determine the effectiveness of a combination of buerger allen and resistance training on fasting blood sugar and hemodialysis adequacy in patients with diabetic kidney disease. Method: This study used a quasi-experimental design with a pre- and post-test and control group. The study was conducted at Pondok Kopi Islamic Hospital in Jakarta, with 59 participants divided into two groups: 32 in the intervention group and 27 in the control group. Both groups underwent fasting blood sugar and hemodialysis adequacy (Kt/V) measurements before and after the combination of Buerger Allen and resistance training. The intervention group performed a combination of Buerger Allen and resistance training for 8 weeks (16 sessions), while the control group received only standard intervention during hemodialysis. Results: The combination of buerger allen exercises and weight training proved effective in lowering fasting blood sugar levels and improving hemodialysis adequacy in patients with diabetic kidney disease. In the intervention group, fasting blood sugar decreased with a mean score difference of 1.75, while the control group experienced an increase of 2.06. Furthermore, there was a significant change in the hemodialysis adequacy score (Kt/V) in the intervention group with a p-value of 0.02. Paired sample results also supported these findings, with the fasting blood sugar (t = 2.11) and Kt/V (t = 2.81) scores showing significant improvements, while the control group showed no significant changes. Overall, the combination of buerger allen exercises and weight training was effective in improving blood sugar control and improving hemodialysis quality in patients with diabetic kidney disease. Conclusion: The combination of buerger allen exercises and weight training was effective in improving blood sugar control and improving hemodialysis quality in patients with diabetic kidney disease. Keywords: Buerger Allen; Diabetic Kidney Disease Patients; Fasting Blood Sugar; Hemodialysis Adequacy; Weight Training. Pendahuluan: Nefropati diabetik adalah istilah lain dari Diabetic Kidney Disease (DKD). Pasien dengan diabetes dan DKD adalah kelompok yang berbeda dari populasi yang didiagnosis dengan salah satu dari dua karakteristik peningkatan ekskresi albumin urin atau penurunan laju filtrasi glomerulus (GFR). Hal ini berdampak pada fungsi ginjal dan mengubah cara pembuangan limbah dan kelebihan cairan dari tubuh. Tujuan: Untuk mengetahui efektivitas kombinasi buerger allen and resistance exercise terhadap gula darah puasa dan adekuasi hemodialisis pasien diabetic kidney disease. Metode: Penelitian ini menggunakan quasi eksperimen dengan rancangan pre and post test group design with control group. Penelitian ini dilakukan di Rumah Sakit Islam Jakarta Pondok Kopi dengan jumlah sampel sebanyak 59 partisipan yang dibagi menjadi 2 kelompok, yakni 32 partisipan pada kelompok intervensi dan 27 partisipan pada kelompok kontrol. Kedua kelompok sampel dilakukan pemeriksaan gula darah puasa dan adekuasi hemodialisis (Kt/V) sebelum dan sesudah kombinasi buerger allen dan resistance exercise. Kelompok intervensi melakukan kombinasi Buerger Allen dan latihan resistensi selama 8 minggu (16 kali pertemuan), sedangkan kelompok kontrol hanya menerima intervensi standar selama hemodialisis. Hasil: Kombinasi buerger allen dan resistance exercise terbukti efektif dalam menurunkan kadar gula darah puasa serta meningkatkan adekuasi hemodialisis pada pasien dengan DKD. Pada kelompok intervensi, terjadi penurunan gula darah puasa dengan selisih mean rank 1.75, sedangkan kelompok kontrol justru mengalami peningkatan sebesar 2.06. Selain itu, terdapat perubahan signifikan pada nilai adekuasi hemodialisis (Kt/V) kelompok intervensi dengan p-value 0.02. Hasil paired sample juga memperkuat temuan ini, nilai t gula darah puasa (t = 2.11) dan Kt/V (t = 2.81), menunjukkan perbaikan bermakna, sementara kelompok kontrol tidak menunjukkan perubahan signifikan. Secara keseluruhan, kombinasi buerger allen dan resistance exercise efektif dalam memperbaiki kontrol gula darah dan meningkatkan kualitas hemodialisis pada pasien DKD. Simpulan: Kombinasi buerger allen dan resistance exercise efektif dalam memperbaiki kontrol gula darah dan meningkatkan kualitas hemodialisis pada pasien DKD. Kata Kunci: Adekuasi Hemodialisis; Buerger Allen; Gula Darah Puasa; Pasien Diabetic Kidney Disease; Resistance Exercise.